IMPLEMENTASI PRAKTIK PERBENGKELAN MESIN BUBUT DI SMK: PERSPEKTIF SOSIAL KONSTRUKTIVISME VYGOTSKY PADA SMK NEGERI 2 KARANGANYAR - Febrianti T. Lestari; Endang Fauziati; Sukasno; Maryadi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Vocational education in Indonesia faces challenges in producing graduates with technical competencies aligned with modern industry needs, particularly in workshop practice learning that remains instructive without considering social aspects and collaborative interactions. This research aims to analyze the implementation of lathe machine workshop practices through Vygotsky's social constructivism perspective at SMK Negeri 2 Karanganyar. Qualitative research methods with case study design were used to explore the implementation of Zone of Proximal Development concepts, scaffolding, and social interaction in practical learning. Data were collected through semi-structured interviews with mechanical engineering teachers and analyzed using thematic analysis techniques. Research results show that students' knowledge construction is realized through structured social interaction, instructors' role as more knowledgeable others with peer tutoring systems, gradual scaffolding implementation through demonstration and physical-symbolic tool mediation, and SMK's socio-cultural context supporting collaborative practice communities. This research concludes that Vygotsky's social constructivism theory effectively enhances students' activity, mutual assistance ability, self-confidence, and independence in lathe machine workshop practices.